Big Facts speak for themselves - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The Big Facts website brings together information on all the big issues to do with climate change, agriculture and food security. Population growth, changing diets, deforestation, food waste and other topics are all there, along with proven successful options for adaptation and mitigation. Add in summaries of the political and financial climates and the Big Facts website is the go-to resource for accurate information. All the facts are derived from scientifically credible sources, with links to more detailed information as well as references to the original sources. Furthermore, in addition to being open access, the entire site is peer reviewed, adding crucial checks and balances. Big Facts also invites improvements, updates and corrections.